In-work Poverty among Immigrants in the EU (Szociológiai Szemle, 2023)
A considerable share of the population is poor in the European Union (EU), among which many are poor despite working. Immigrants are overrepresented among the working poor. Working immigrants dispose lower equivalent household income on average and face higher risks of falling into poverty than working natives, according to a cross-sectional regression analysis on a sample of 22 EU member states in 2011 (based on EU-SILC 2012). The differential between the two groups shrinks considerably, though does not disappear, when controlling for micro level factors (socio-demographic characteristics such as attained education level, occupation, household size) of the level of household income and the risk of in-work poverty. The income gap underlines the need for better social inclusion of immigrants.